Drugs and crime - Bean, Philip, 1936- (Abingdon, Oxon : Routledge, 2014)
This book provides an authoritative and much-needed overview of the range of issues associated with drugs-related crime. The author pays particular attention to policing drugs and drug markets and the way they operate, so that a central theme of the book is the importance of reducing supply at local, national and international levels. Accordingly there are chapters on the drugs-crime link, sentencing offenders, policing drug offenders including the use of informers, coercive treatment, trafficking and laundering, and on gender issues, including the treatment of women drug users.' This updated and expanded new edition builds upon the strengths of earlier editions of the book. It has been updated throughout, includes new information on police tactics such as'stop and search' and'test purchase', and has an entirely new chapter on the legalisation debate.
Drugs and crime: an overview -- Sentencing drug offenders -- Drugs and crime: theoretical formulations -- Treatment in criminal justice -- Drug courts and drug testing -- Trafficking, laundering and confiscation -- Drug markets and policing -- Informers and corruption -- Women, drugs and crime -- The legalisation debate -- Suggestions for the way forward.
Includes bibliographical references (pages 281-297) and indexes.
Keywords: Drug abuse and crime -- United Kingdom